Role and value of whole genome sequencing in studying tuberculosis transmission. (November 2019) - Nikolayevskyy, V.; Niemann, S.; Anthony, R.; van Soolingen, D.; Tagliani, E.; Ködmön, C.; van der Werf, M.J.; Cirillo, D.M.
Abstract: Background: Tuberculosis (TB) remains a serious public health threat worldwide. Theoretically ultimate resolution of whole genome sequencing (WGS) for Mycobacterium tuberculosis complex (MTBC) strain classification makes this technology very attractive for epidemiological investigations. Objectives: To summarize the evidence available in peer-reviewed publications on the role and place of WGS in detection of TB transmission. Sources: A total of 69 peer-reviewed publications identified in Pubmed database. Content: Evidence from >30 publications suggests that a cut-off value of fewer than six single nucleotide polymorphisms between strains efficiently excludes cases that are not the result of recent transmission and could be used for the identification of drug-sensitive isolates involved in direct human-to-human TB transmission. Sensitivity of WGS to identify epidemiologically linked isolates is high, reaching 100% in eight studies with specificity (17%–95%) highly dependent on the settings. Drug resistance and specific phylogenetic lineages may be associated with accelerated mutation rates affecting genetic distances. WGS can be potentially used to distinguish between true relapses and re-infections but in high-incidence low-diversity settings this would require consideration of epidemiological links and minority alleles. Data from four studies looking into within-host diversity highlight a need for developing criteria for acceptance or rejection of WGS relatedness results depending on the proportion of minority alleles. Implications: WGS will potentially allow for more targeted public health actions preventing unnecessary investigations of false clusters. Consensus on standardization of raw data quality control processing criteria, analytical pipelines and reporting language is yet to be reached.